Five Additions to Southwestern Pennsylvania Naiad Fuana - Don P. Tanner (Hello World!, 1970)
Lastena lata Raf. 1820; Simpsoniconcha ambigua (Say. 1825); Carunculina parva (Barnes, 1823); Lasmigona compressa (Lea, 1829), and Anodonta umbecillis Say, 1829 were found in various situations during the past year.